Dinamika Akuntabilitas Pemerintah Desa dalam Implementasi Desentralisasi di Indonesia - Hendri Gunawan; Aldri Frinaldi; Lince Magriasti; Hendra Naldi (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the dynamics of village government accountability in implementing decentralization in Indonesia. Decentralization has expanded village authority in governance, financial management, public services, development, and community empowerment, yet this authority also raises demands for transparent and responsible governance. The study aims to analyze how village government accountability is formed, challenged, and strengthened within the decentralization framework. This research employs a descriptive qualitative approach through a narrative-structured literature review. Data were obtained from 410 scientific journal articles and official statistical data on village potential and village government finance. VOSviewer was used to map keyword relationships and identify dominant themes in the reviewed literature. The findings show that village accountability is multidimensional and closely related to transparency, government performance, supervision, institutional capacity, community participation, public service delivery, infrastructure, and village development. The VOSviewer mapping identifies three main clusters: accountability, transparency, and performance; government-community relations; and village governance capacity, including human resources, regulation, public services, infrastructure, challenges, and obstacles. Statistical data indicate that Indonesian villages have substantial economic potential, local products, village-owned enterprises, and public assets, but they also face fiscal dependence on transfer funds, unequal infrastructure, weak telecommunication access, environmental risks, and uneven administrative capacity. The study implies that strengthening village accountability cannot rely only on formal reporting. It requires open information, stronger supervision by village consultative bodies, improved capacity of village officials, and meaningful community participation to support accountable, responsive, and sustainable village governance in diverse rural areas across Indonesia and improve public trust nationally at the local level.